Eksistensi Sertifikat Elektronik Terhadap UU Cipta Kerja Dalam Menjamin Kepastian Hukum - Qonita Rizkiana; Widhi Handoko (Notarius, 2023)
Abstract Land is an important element in human life, especially land administration, the Government provides Land Registration program, however, there are still many problems, especially in the form of certificates as evidence of rights, so that the Minister of Atr/Head of Bpn Regulation No. 1 of 2021 concerning Electronic Certificates, which stipulates the change of Analog Certificates to Electronic Certificates. Which proclaimed the change of formaat Certificates, as well as derivatives of Article 147 of the Job Creation Law. Which has many problems so that it still requires further research as What is the Existence of Electronic Certificates according to the Job Creation Act? And what is the role of Electronic Certificates in the Job Creation Act for legal certainty? The purpose of this research is to find out the existence of electronic certificates according to the Job Creation Act and the role of Electronic Certificates to the Job Creation Law to ensure legal certainty. The method in this research is the normative juridical method, which uses legal materials in solving legal facts and problems, and uses literature study analysis. The results of the study show that the Importance of Electronic Certificates to the Job Creation Act in Creating Legal Certainty.Keywords: certificate; electronic certificate; copy right.AbstrakTanah merupakan elemen penting dalam kehidupan manusia, terutama administrasi pertanahan, Pemerintah memiliki program Pendaftaran Tanah, namun, dalam penerapannya masih terdapat banyak masalah, terutama dalam bentuk sertifikat sebagai bukti hak, sehingga Menteri ATR/Kepala BPN Nomor 1 Tahun 2021 tentang Sertifikat Elektronik, yang mengatur perubahan Sertifikat Analog menjadi Sertifikat Elektronik. Memproklamirkan perubahan format Sertifikat, serta turunan dari Pasal 147 UU Cipta Lapangan Kerja. Tujuan penelitian ini untuk mengetahui keberadaan sertifikat elektronik sesuai UU Cipta Lapangan Kerja dan peran sertifikat elektronik dalam UU Cipta Lapangan Kerja untuk kepastian hukum? Tujuan penulisan adalah untuk mengetahui keberadaan sertifikat elektronik sesuai UU Cipta Lapangan Kerja dan peran Sertifikat Elektronik terhadap UU Cipta Lapangan Kerja untuk menjamin kepastian hukum. Metode yuridis normatif digunakan sebagai metode dalam penelitian ini, menggunakan bahan hukum dalam memecahkan fakta dan masalah hukum, dan menggunakan analisis studi literatur. Hasil penelitian menunjukkan bahwa Pentingnya Sertifikat Elektronik terhadap UU Cipta Lapangan Kerja dalam Menciptakan Kepastian Hukum.Kata kunci: sertifikat; sertifikat elektronik;  cipta kerja.